The ecology and evolution of the monito del monte, a relict species from the southern South America temperate forests - Fontúrbel, Francisco E. (2022)
The arboreal marsupial monito del monte (genus Dromiciops, with two recognized species) is a paradigmatic mammal. It is the sole living representative of the order Microbiotheria, the ancestor lineage of Australian marsupials. Also, this marsupial is the unique frugivorous mammal in the temperate rainforest, being the main seed disperser of several endemic plants of this ecosystem, thus acting as keystone species. Dromiciops is also one of the few hibernating mammals in South America, spending half of the year in a physiological dormancy where metabolism is reduced to 10% of normal levels. This capacity to reduce energy expenditure in winter contrasts with the enormous energy turnover rate they experience in spring and summer. The unique life history strategies of this living Microbiotheria, characterized by an alternation of life in the slow and fast lanes, putatively represent ancestral traits that permitted these cold-adapted mammals to survive in this environment. Here, we describe the ecological role of this emblematic marsupial, summarizing the ecophysiology of hibernation and sociality, updated phylogeographic relationships, reproductive cycle, trophic relationships, mutualisms, conservation, and threats. This marsupial shows high densities, despite presenting slow reproductive rates, a paradox explained by the unique characteristics of its three-dimensional habitat. We finally suggest immediate actions to protect these species that may be threatened in the near future due to habitat destruction and climate change.